LEGAL REFORM ON THE CONCEPT OF RESTORATIVE JUSTICE IN THE CRIMINAL JUSTICE SYSTEM - Adhi Wibisana, Anak Agung Ngurah; Wisnumurti, Anak Agung Gede Oka; Budiartha, I Nyoman Putu; Dewi, Anak Agung Sagung Laksmi (Jurnal Pembaharuan Hukum, 2024)
Restorative justice is an alternative to solving criminal cases, which in the resolution mechanism involves the perpetrator, victim, perpetrator’s family, victim’s family, community leaders, or stakeholders to jointly find a fair solution and emphasize returning to the situation as before. The implementation of the concept of restorative justice is needed in an effort to reform the law of the criminal justice system. This study aims to understand, explain, analyze, and make a comparison with the implementation of the concept of restorative justice as an effort to reform criminal law. The method used in this study is normative legal research. There are efforts to reform the law or legal findings in a criminal justice system regarding the resolution of criminal cases. The concept of restorative justice can be adopted and simultaneously applied. In addition to minimizing the accumulation of case files, restorative justice prioritizes the rights of perpetrators and victims and the restoration of the situation.